Gender, diversity and trade unions : international perspectives - Colgan, Fiona; Ledwith, Sue (Routledge research in employment relations, 2003)
This book brings together research in gender, race, ethnicity, sexuality, disability and the growing intersection between trade unions and social movements. It offers an authoritative basis for comparative analysis in eleven countries.